Distinct Antiviral Properties of Two Different Bacterial Lysates - Michael Roth; Hanif J. Khameneh; Lei Fang; Michael Tamm; Giovanni A. Rossi (Canadian Respiratory Journal)
Oral bacterial lysates (OBLs) can reduce the frequency and severity of recurrent respiratory tract infections in children from viral and bacterial origins. OBL-induced early innate immune reaction was already shown, but the specific features of different OBLs have never been studied and compared. A study was conducted to assess in vitro the protective effects on rhinovirus- (RV-) infected human bronchial epithelial cells (BECs) of two slightly different OBLs: OM-85 and Pulmonarom. Furthermore, since immune cells represent the key arm for antiviral defence, the capacity of these OBLs to induce selected cytokine production in mouse bone marrow-derived DCs (BMDCs) was also evaluated. Although different OBLs may share some mechanisms to protect host cells from virus infection, some product-specific antimicrobial activities were observed on RV-infected human BECs and mouse BMDCs. These results are consistent with a product-specific response possibly triggered by different pathogen-associated molecular patterns (PAMPs) contained in OBLs.